Carbon Quantum Dot Incorporated Nickel Pyrophosphate as Alternate Cathode for Supercapacitors. Issue 8 (27th February 2020) - Priyadharshini, Matheswaran; Pazhanivel, Thangavelu; Bharathi, Ganapathi
Abstract: In spite of its large theoretical capacitance, the crystal structure of transition metal pyrophosphates frequently endures sluggish charge transfer and volume expansion leading to severe structural instability which may be ascribed to low power density and constant intercalation and deintercalation of ions in the matrix. Due to the stated facts, it resulted in quick capacity degradation and limited the overall performance of the energy device. To overcome the stated facts, we report the electrochemical charge storage performances of Nickel pyrophosphate/Carbon quantum dot (Ni2 P2 O7 /CQD) nanocomposites. Here, we adopted a facile technique to prepare biowaste derived CQD and composited it with transition metal (Nickel) pyrophosphate. Incorporation of carbon quantum dots not only increased the specific capacitance than bare, besides, it also provides a long‐run cyclability. The addition of CQDs to the matrix favors rapid charge transfer and buffered the mechanical stress of nanocomposite. Using power law, the capacitance contribution from diffusion‐controlled and capacitive type mechanisms to the total specific capacitance was also elucidated. Hence the cost‐effective, facile synthesis method and favorable redox reaction empowered with voltage would have a potential application in high energy devices. Abstract : Carbon quantum dots (CQD) were prepared from biowaste (orange peel) with size ranging from 2–3 nm. The facile hydrothermal technique was adopted for the synthesis of Ni2 P2 O7 and Ni2 P2 O7 /CQD composite material. The addition of CQDs to the Nickel Pyrophosphate favours a rapid charge transfer and buffered the mechanical stress during charging and discharging of active electrode. Using power law, the capacitance contribution from diffusion‐controlled and capacitive type mechanisms to the total specific capacitance was also elucidated.